Competitive Intensity, Innovation Capability and Dynamic Marketing Capabilities - Ari Riswanto (Publindo Akademika, 2021)
Competition intensity (CI), innovation capability (IC) and dynamic marketing capabilities (DMCs) are still an interesting problem for studies in scientific research. This study aims to determine the extent of the ability of innovation in mediating the effect of the intensity of competition on dynamic marketing skills. Quantitative descriptive becomes the method used in this study, with simple linear regression analysis and SPSS v 23 and Amos v. 23 software as a calculation tool, beginning with the measurement of the model using Confirmatory Factor Analysis (CFA) and Product of Coefficient Strategy analysis: Single Mediation Model, with a sample of 189 MSMEs engaged in the processing industry in Sukabumi. This study shows that the innovation capability variable (IC) can mediate the influence of competition intensity (CI) on dynamic marketing capabilities (DMCs) on MSMEs in Sukabumi, West Java, Indonesia in 2018.